The Role of Health Information Systems in Improving Medication Safety During Anesthesia - Ahmed Alasiri, Ahmed Ibrahim; Ahmed Alfaifi, Hatim Yahya; Mohammed Asiri, Khalid Ali; Hadi Alabatahin, Saleh Saeed; Ali Shuqayfi, Adel Hamad; Yahya Gasem, Othman Ibrahim; Shamla Kuriry, Mohammed Hadi Ali Abu; H Alyami, Rashed Mahdi (Journal of Neonatal Surgery, 2025)
Introduction: Patient safety in anesthesia has been threatened by medication errors that are severe as the administration of strong medications often occurs immediately and there is no time to recover after the mistake. Sixty-nine percent of anesthesia clinicians in Saudi Arabia report having committed at least one drug error throughout their career with the key issues cited being haste, heavy workload, and poor communication. The Kingdom is actively embracing Health Information Systems (HIS) in an attempt to curb these risks and standardise perioperative care under the Saudi Vision 2030 framework. Study Objective: By conducting this systematic review, we will have a comprehensive understanding of how Health Information Systems (HIS) are currently utilized in the Kingdom of Saudi Arabia, including Electronic Health Record (EHR), Anesthesia Information Management System (AIMS) to improve the safety of drugs administered in anaesthesia. Methodology: The review examined peer-reviewed clinical research data, institutional cohort data of large tertiary centers such asKing Faisal Specialist Hospital and Research Center (KFSHRC) and national policy papers of the Saudi Food and Drug Authority (SFDA) and the Saudi Patient Safety Center (SPSC). The analysis concentrated on the quantitative measures, including the rate of documentation completion, the rate of error interception, and the satisfaction of users. Conclusion: HIS has shown a strong potential of decreasing human error and enhancing the quality of perioperative data in Saudi Arabia. Nevertheless, the maximum levels of their safety require human factor consideration, e.g., burnout, optimization of user interfaces to avoid alert fatigue, and non-punitive culture of reporting, instead of observing the fear of errors and teaching it to the organization